Different Textile Materials as Light Shaping Attachments in Studio Photography and Their Influence on Colour Reproduction - Veronika Štampfl; Klemen Možina; Jure Ahtik (Tekstilec)
The research focuses on the quality of colour reproduction when using different light sources, often used to illuminate scenes in a photo studio, and different types of fabrics as lighting shapers. With the latter, the light can be converted into softer and more diffuse light, but the properties of the fabrics used affect the colour impression and thus the quality of the reproduced colours. This was evaluated by analysing the colour differences which were calculated from the colorimetric values of the colour patches of the X-Rite ColorChecker Passport test chart. Test chart was photographed in a controlled environment and illuminated with different combinations of light sources and tested fabrics. The results confirmed that not all combinations of variables are suitable for use if the goal of the photograph is to achieve high quality colour reproduction.